If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 3)(4x + -16) = 0 Reorder the terms: (3 + x)(4x + -16) = 0 Reorder the terms: (3 + x)(-16 + 4x) = 0 Multiply (3 + x) * (-16 + 4x) (3(-16 + 4x) + x(-16 + 4x)) = 0 ((-16 * 3 + 4x * 3) + x(-16 + 4x)) = 0 ((-48 + 12x) + x(-16 + 4x)) = 0 (-48 + 12x + (-16 * x + 4x * x)) = 0 (-48 + 12x + (-16x + 4x2)) = 0 Combine like terms: 12x + -16x = -4x (-48 + -4x + 4x2) = 0 Solving -48 + -4x + 4x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '4'. 4(-12 + -1x + x2) = 0 Factor a trinomial. 4((-3 + -1x)(4 + -1x)) = 0 Ignore the factor 4.Subproblem 1
Set the factor '(-3 + -1x)' equal to zero and attempt to solve: Simplifying -3 + -1x = 0 Solving -3 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -1x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -1x = 0 + 3 -1x = 0 + 3 Combine like terms: 0 + 3 = 3 -1x = 3 Divide each side by '-1'. x = -3 Simplifying x = -3Subproblem 2
Set the factor '(4 + -1x)' equal to zero and attempt to solve: Simplifying 4 + -1x = 0 Solving 4 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + -1x = 0 + -4 Combine like terms: 4 + -4 = 0 0 + -1x = 0 + -4 -1x = 0 + -4 Combine like terms: 0 + -4 = -4 -1x = -4 Divide each side by '-1'. x = 4 Simplifying x = 4Solution
x = {-3, 4}
| 2/5h-7=13 | | Y=-2x^2-12x-23 | | 1.875=5/8(b-5) | | 12x+16=31 | | b/3=3 | | u/8=2 | | 6(y-3)=2(19-y) | | c-9=3/4c | | t/4=32 | | 2y-(13-2y)=59 | | (x+2)+y= | | 6r+4s= | | (143(5)+67)=5 | | y^2-1y-42=0 | | 5/3+6/10 | | 4(2x-5)=16 | | 1/4(9x+3)=3x+1 | | 3x(x+7)=21 | | (3x+1)/10=(x-1)/7 | | 5-(4-8x)=4x+2 | | 4y+3X=197 | | 8/17dividedby10/6 | | 8/17/10/6 | | (-2c+3d/3c)+(9c-4d/9c)+2 | | 4-8+0= | | 3(x^2-64)=0 | | 1/2(6a | | 1/2(6a2-4a+5)= | | 4x-64906-488=2 | | 3(x^2-64)=00 | | 8-h/3=19 | | 9.4minusk=3 |